A comparison of sexual function in primiparous and multiparous women. (2nd April 2020) - Banaei, Mojdeh; Alidost, Farzane; Ghasemi, Erfan; Dashti, Sareh
Abstract: Childbirth is one of the most important influencing factors for sexual function. Therefore, this study was conducted with the aim of comparing sexual function in primiparous and multiparous women. This cross-sectional analytical study was performed using systematic random sampling on 420 women in the postpartum period who referred to Bandar Abbas health Centres in 2018. The data were collected using an interview method which consisted of a Female Sexual Function Index questionnaire and a demographic questionnaire. The data analysis was performed using the SPSS Version 23 software. The results showed that sexual dysfunction was lower in multiparous women compared to primiparous women ( p  = .006). Low sexual activity in primiparous women can be due to less privacy and more time and energy loss. Several factors including housing situation, monthly income, episiotomy incision, and the education level of the couple were influential in the sexual function of the primiparous women ( p  < .05). Sexual function differs between primiparous and multiparous women in postpartum period and the number of deliveries can affect sexual performance. IMPACT STATEMENT: What is already known on this subject? Sexual function in humans is affected by a complexity of interactions. Childbirth is among the most one of the important factors that influences sexual function. Pregnancy and childbirth affect all organs of the female body, especially the genital tract, and the resulting changes may cause problems in sexual intercourse. Negative childbirth experiences from previous deliveries can affect sexual performance. What do the results of this study add? Regarding the high prevalence of sexual problems during the postpartum period and the direct impact of this on spousal relationship, and also given the controversial data on the relationship between parity and sexual dysfunction, the present study was conducted to compare postpartum sexual function between primiparous and multiparous women. What are the implications of these findings for clinical practice and/or further research? The sexual and emotional intimacy of couples may be affected due to the changes in women's sexual function as the result of physiological and anatomical changes during pregnancy and postpartum. Therefore, to improve the quality of sexual relations, screening and counselling for sexual disorders should not be limited to pregnancy and postpartum periods, but should also be included in pre-pregnancy counselling centres.